The Application of Mathematics in Economic Science - Subakti, Jani; Wibowo, Agung; Hanifan, M. Zakie (INOVATOR, 2025)
Mathematics is an essential foundation for modern economic analysis. Through a mathematical approach, the relationships between economic variables can be explained quantitatively and logically. This study aims to examine the application of mathematics in economics, particularly in the context of microeconomics and macroeconomics. The method used is descriptive qualitative, with a literature review approach from various academic sources. The results of the study indicate that the application of mathematics helps economists analyze market behavior, predict economic changes, and formulate more rational policies. Mathematical models such as the demand-supply function, elasticity analysis, and the Solow growth model are concrete examples of how mathematics strengthens economic science